Practicing Safe Sects Religious Reproduction in Scientific and Philosophical Perspective - Shults, F.LeRon (Philosophical Studies in Science and Religion, 2018)
In Practicing Safe Sects F. LeRon Shults provides scientific and philosophical resources for having "the talk" about religious reproduction: where do gods come from - and what are the costs of bearing them in our culturally pluralistic, ecologically fragile environment?; Readership: All interested in the promotion of peaceful and healthy societies, and anyone concerned with the role of religion in fostering superstition and segregation.